Understanding the Extent and Drivers of Interphysician Cost Variation for Spine Procedures. Issue 13 (July 2016) - Kazberouk, Alex; Sagy, Iftach; Novack, Victor; McGuire, Kevin
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: Retrospective analysis of billing data, medical records, and hospital cost data. Objective: To quantify intersurgeon variation for hospital costs of four spine procedures while adjusting for patient comorbidities and demographic factors. Summary of Background Data: Spine care accounts for $90 billion in health care expenditures in the United States. Past findings demonstrate regional variation in surgery rates and high intersurgeon variation for anterior cervical discectomies/fusions. However, less has been done to examine intersurgeon variation in resource use across multiple procedures while adjusting for patient characteristics outside of a surgeon's control. Methods: We examined intersurgeon variation for 1241 elective spine procedures at one facility for 3 years. The procedures included 1 to 2 level cases of anterior cervical discectomies/fusions, posterior lumbar decompressions/fusions, posterior laminectomies, and lumbar discectomies. We isolated mean and median costs by surgeon and adjusted for patient demographics, comorbidities, and procedure types. Finally, we examined variation in subcategories such as instrumentation and inpatient stay costs to determine which contribute to total cost variation. Results: Unadjusted costs per surgeon varied by a factor of 1.32 to 1.81 between lowest and highest cost surgeon depending on procedure. After adjusting for patient features and procedure, variation was reduced to 1.31x. Of the seven surgeons who had sufficient patient volume, one was significantly less costly (−$1, 462 per procedure) whereas three were significantly more costly than mean (+$685, +$839, +$702 per procedure). Intersurgeon differences in supply and operating room costs largely accounted for total variation, though actual drivers of variation were surgeon-specific. Conclusion: Surgeons vary in average cost for spine procedures, though variation is more modest once adjusted for patient characteristics. Data on procedure-level variation should be discussed with individual surgeons to shift practice patterns. Finally, the comparison methodology can be applied to other procedures and specialties. Level of Evidence: 4